ٌ - Argumentative Bonds And Factors In The Prophet Muhammad's ﷺ Hadith: "indeed, Eloquence Is A Kind Of Magic" – A Pragmatic Approach - harrar, nassim (El Omda in Linguistics and Discourse Analysis, 2025)
Argumentative discourse and its impact on guiding the path of inference and persuasion. The research aims to present a comprehensive theoretical conception of the nature of these mechanisms, their classifications, and their linguistic and pragmatic characteristics, while highlighting the possibility of considering them a performative approach in analyzing linguistic discourses. Among the results achieved, we mention: that argumentative connectors and operators form a cohesive fabric of the argumentative structure, contributing to the production of specific argumentative significations that transcend the direct lexical meaning of utterances. Furthermore, the study of argumentative connectors and operators represents a frontier for innovation in Arabic linguistic studies.